Chloroplast-rich material from the physical fractionation of pea vine ( Pisum sativum ) postharvest field residue (Haulm) - Torcello-Gómez, Amelia; Gedi, Mohamed A.; Ibbett, Roger; Nawaz Husain, Khatija; Briars, Rhianna; Gray, David (Elsevier, 2019)
An innovative procedure for plant chloroplasts isolation has been proposed, which consists of juice extraction by physical fractionation from plant material and recovery of its chloroplast-rich fraction (CRF) by centrifugation. This simple method has been applied to pea vine haulm subjected to different post-harvest treatments: blanching, storage at different relative humidity values and fermentation. Additionally, freeze storage of the extracted juice was carried out. The macronutrient (total lipids, proteins, ash and carbohydrates) and micronutrient (fatty acids, chlorophylls, β-carotene, α-tocopherol and ascorbic acid) content and composition of the CRF have been determined. The CRF isolated from fresh pea vine haulm is a potential source of essential micronutrients (α-linolenic acid, β-carotene, α-tocopherol) and carbohydrates, whereas the post-harvest treatments trialled have a detrimental effect on the nutritional content. Industrial applications for the recovered nutritionally rich fraction, such as food supplement ingredient or animal feeding, are likely envisaged, while optimising the use of green haulm.